Distal Femoral Pin Tracker Placement Prevents Pin Tract-induced Fracture in Robotic-Assisted Total Knee Arthroplasty - Baek, Ji-Hoon; Lee, Su Chan; Kim, Jin-Hong; Ahn, Hye Sun; Nam, Chang Hyun (The Journal of Knee Surgery, 2021)
The purpose of this study was to determine the effectiveness of the placement of pin trackers in the medial sagittal plane of the distal femur in robotic-assisted total knee arthroplasty (TKA) over a minimum follow-up period of 3 months. From August 2020 to October 2020, a consecutive series of 81 TKAs were performed in 59 patients using the Triathlon posterior-stabilized total knee prosthesis with a robotic-assisted system (Mako) at our hospital. Patient charts were reviewed for complications associated with the pin sites, including fracture, infection, thigh pain, and the need for reoperation. No patients had any minor or major complications associated with distal femoral pins. This technique, which used pin trackers in the medial sagittal plane of the distal femur, could be a useful option for surgeons performing robotic-assisted TKA. This is a Level IV study.
Keywords: total knee arthroplasty; robotic-assisted system; complications